Analisis Kualitas Pelayanan Publik Kantor Keuchik Gampong Empee Trieng Berdasarkan Asas Penyelenggaraan Pemerintah Pada Pelayanan Umum - Permana, M. Ade; Masni, Melly (Jurnal Riset dan Pengabdian Masyarakat, 2021)
The government is expected to develop a public service paradigm from a centralized service to a service that focuses more on community satisfaction-oriented management. Moreover, the village apparatus (gampong in Acehnese language) as part of the state apparatus has a direct relationship so that they should better understand the living conditions of the people who are within the scope of their administration. In this case, the author takes a case study of the Gampong Empee Trieng Government, where the author performed community service tasks. To meet the demands of excellent administrative services, Gampong government officials are required to provide good services, especially in providing professional services, having work systems and service procedures that are transparent, integrated, responsive, and adaptive to any changes. This study uses a descriptive approach with qualitative research that will provide an overview of how the performance of the Gampong Empee Trieng government in improving the quality of public services for its people. The three principles of government administration that focus on public services will be used as indicators to measure the quality of public services in Gampong Empee Trieng, Darul Kamal District, Aceh Besar District.